Experimental Study on the Mechanical Properties and Damage Evolution of Hollow Cylindrical Granite Specimens Subjected to Cyclic Coupled Static-Dynamic Loads - Yongming Xue; Bing Dai; Ying Chen; Lei Zhang; Guicheng He; Zhijun Zhang (Geofluids)
To study the characteristics of roadway surrounding rock damage caused by frequent disturbances under different static stress conditions, cyclic impact tests on granite with vertical holes under different axial prestress conditions were performed by a modified split Hopkinson pressure bar test, and the damage of the specimens was recorded with a high-speed camera process. The test results show that under the same air pressure cyclic impact, the rock specimens mainly undergo the compaction-fatigue-failure transition. As the axial prestress increases, the compaction-fatigue phase gradually weakens, and the dynamic compressive strength decreases. When the axial prestress is 42% of the UCS and 62% of the UCS, the rock specimen shows a certain “strengthening” effect during the initial cyclic impact stage. During the failure of the rock specimens, the axial prestressing effect limited the initiation of some transverse cracks, and a mixed tensile-shear failure mode appeared. The rock specimens with an axial prestress of 62% of the UCS showed energy release during cyclic impact. To some extent, the probability of “rock bursts” has been induced. Based on the one-dimensional stress wave theory, the damage variables of wave impedance during the cyclic impact loading of the rock with vertical holes are defined. It is found that when the rock specimen is in the stage of compaction and fatigue damage, the damage is small, and the damage is even reduced.